Radiological comparison of a FDNPP waste storage site during and after construction. (December 2018) - Connor, D.T.; Martin, P.G.; Pullin, H.; Hallam, K.R.; Payton, O.D.; Yamashiki, Y.; Smith, N.T.; Scott, T.B.
Abstract: The clean-up effort that is occurring across the region affected by the 2011 Fukushima Daiichi Nuclear Power Plant accident is unprecedented in its magnitude as well as the financial cost that will eventually result. A major component of this remediation is the stripping of large volumes of material from the land surface, depositing this into large waste storage bags before placing these 1 cubic meter bags into specially constructed stores across Fukushima Prefecture. In this work, using an unmanned aerial vehicle to perform radiological surveys of a site, the time-resolved distribution of contamination during the construction of one of these waste storage sites was assessed. The results indicated that radioactive material was progressively leaching from the store into the surrounding environment. A subsequent survey of the site conducted eight months later revealed that in response to this survey and remedial actions, the contamination issue once existing on this site had been successfully resolved. Such results highlight the potential of low-altitude unmanned aerial systems to easily and rapidly assess site-wide changes over time – providing highly-visual results; therefore, permitting for prompt remedial actions to be undertaken as required. Use of UAV radiation mapping and airborne photogrammetry to produce a time-resolved assessment of remediation efforts within a Fukushima temporary storage facility. Graphical abstract: Image 1 Highlights: Time-resolved waste-store monitoring. Impact of subsequent remedial work assessed. Impact of imported material on radiological signature. 3D model of site with radiation overlay produced. High-resolution "difference map" of the site constructed.